MUDIK LEBARAN: STUDI KUALITATIF - Bambang Bemby Soebyakto (Department of Development Economics, Universitas Sriwijaya, 2011)
This study analyze the behavior of the community and benefit from the Mudik. Where research is qualitative by incidental sampling method that is getting